Exploring Conversational Implicatures in the American Sitcom Seinfeld - Cezar, Leticia Mello (BELT - Brazilian English Language Teaching Journal, 2021)
Since learners must know how to use language in different contexts, sitcoms could help with pragmatic competence development because they display contextualized lifelike language. Could identifying conversational implicatures in a sitcom help develop metalinguistic awareness of implicatures? In addition, are there conversational implicatures in the sitcom Seinfeld that present the potential to help develop pragmatic competence? This article illustrates conversational implicatures through Seinfeld episodes and discusses how identifying implicatures could develop metapragmatic awareness. The method was a descriptive research of the qualitative type. Ten segments from the American sitcom Seinfeld were analyzed based on their conversational implicature occurrence. The implicatures present in the segments are discernible and may help develop pragmatic competence if explicitly taught to learners. Further studies could focus on quantitative research in EFL classrooms on the potential benefits of using sitcoms to develop metalinguistic awareness.